Maternal common variant rs2305957 spanning PLK4 is associated with blastocyst formation and early recurrent miscarriage - Zhang, Qian; Li, Guangyu; Zhang, Lei; Sun, Xiaohe; Zhang, Dandan; Lu, Juanjuan; Ma, Jinlong; Yan, Junhao; Chen, Zi-Jiang (Fertility and sterility, 2017)
To investigate whether the common variant rs2305957 spanning PLK4 (Polo-like kinase 4) confers risk to embryo development in Northern Chinese Han (CHN) women. Genetic association study. University hospital. A total of 2,015 infertile women who underwent in vitro fertilization (IVF), 530 women with early recurrent miscarriage (ERM), and 600 fertile control women in the CHN population. Genotyping of rs2305957 was performed by means of high-resolution melting analysis. Blastocyst formation, implantation, early miscarriage, and live birth rates in infertile women; genotype distribution at rs2305957 in ERM case and control subjects. In the first cohort of this study, infertile women with AA genotype had a lower blastocyst formation rate than those with AG or GG genotype. No significant differences were observed in implantation rate, early miscarriage rate, or live birth rate among AA, AG, and GG subgroups. In the second cohort, common variant rs2305957 was related to ERM. Genotype frequency differences were also significant in both additive model and dominant model. Common variant rs2305957 is associated with blastocyst formation and ERM in CHN women. Further investigations of PLK4 gene during embryo development could be worthwhile.